2020
DOI: 10.1021/acs.est.9b05755
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Energy Balance: Environmental Trade-Offs of Organics Capture and Low Carbon-to-Nitrogen Ratio Sewage Treatment Systems

Abstract: Several life-cycle assessments (LCAs) have evaluated the environmental impacts (EIs) of different wastewater treatment (WWT) configurations, attempting resource recovery and energy efficiency. However, a plant-wide LCA considering up-concentration primary treatment and low carbon-to-nitrogen (C/N) ratio sewage at the secondary biological treatment (SBT) has not yet been conducted. This study identifies the environmental trade-offs and hotspots for the chemically enhanced primary treatment (CEPT) and low C/N ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The water-carbon-pollution nexus could seek holistic and integrated solutions to sewage and sludge treatment and waste management. Several research in terms of the nexus and impacts on the SDGs refer to urban municipal sewage treatment (Singh et al 2016 ; Alvarado et al 2020 ), cement waste treatment (Brunner and Rechberger 2015 ), medical waste treatment (Yao et al 2020 ), food waste management, and organic sludge management (Cieślik et al 2015 ). In general, the water-carbon-pollution nexus is not only associated with SDG 7 and SDG 12 directly, but also is indirectly connected with SDG 11 and SDG 13, as shown in Fig.…”
Section: Importance Of Nexus Thinking In Wc Toward Sdgsmentioning
confidence: 99%
“…The water-carbon-pollution nexus could seek holistic and integrated solutions to sewage and sludge treatment and waste management. Several research in terms of the nexus and impacts on the SDGs refer to urban municipal sewage treatment (Singh et al 2016 ; Alvarado et al 2020 ), cement waste treatment (Brunner and Rechberger 2015 ), medical waste treatment (Yao et al 2020 ), food waste management, and organic sludge management (Cieślik et al 2015 ). In general, the water-carbon-pollution nexus is not only associated with SDG 7 and SDG 12 directly, but also is indirectly connected with SDG 11 and SDG 13, as shown in Fig.…”
Section: Importance Of Nexus Thinking In Wc Toward Sdgsmentioning
confidence: 99%
“…All sectors are actively pursuing decarbonization goals to address climate change; among such goals, there is an urgent emphasis on developing wastewater treatment systems that achieve carbon neutrality. , Municipal wastewater treatment plants (WWTPs) are energy-intensive; they consume approximately 3% of the total electricity in most countries . Therefore, it is necessary to amalgamate simple, principle-based, and advanced technologies with conventional processes to enhance the energy self-sufficiency of municipal WWTPs. Sidestream anaerobic digestion (AD) of sludge with methane production is the most commercialized approach for bioenergy recovery in WWTPs, which can be coupled with a combined heat and power (CHP) process to offset their partial energy consumption. The energy recovery potential from this traditional pathway can be effectively maximized by using two strategies: redirecting organic matter from mainstream oxidation to sidestream methane production and upgrading the treatment efficiency of the AD reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Various concentration alternatives have been reported to reinforce organic matter capture, such as high-rate activated sludge, chemically enhanced primary treatment (CEPT), and membrane filtration . Of these, CEPT is regarded as a simple and effective method for capturing organic matter and phosphorus by adding coagulants into extant primary sedimentation facilities. , However, the addition of coagulant in CEPT represents 55% of the total operation cost of a novel WWTP (at 0.03 €/m 3 of wastewater) . It is thus necessary to address two urgent issues: the high chemical costs and huge amount of inorganic sludge produced at high coagulant dosages. Aluminum or iron coagulants can be recycled through the direct chemical acidification of CEPT sludge. , Aluminum-containing acidic sludge, however, is unsuitable for subsequent use in the AD process .…”
Section: Introductionmentioning
confidence: 99%
“…For example, technologies for methane recovery such as degassing membranes are often included within system boundaries to reduce the GHG emissions associated with AnMBR. Alvarado et al. found that SAF-MBR with PNA had the lowest environmental impact among tested configurations, and Cogert et al found that AnMBR and PNA could be paired further with DAMO to achieve similarly low life cycle impacts. , Pretel et al also evaluated DAMO and included phosphorus precipitation within system boundaries . While these studies incorporated nitrogen removal within the context of anaerobic secondary treatment trains, sulfide was largely neglected in these studies.…”
Section: Introductionmentioning
confidence: 99%